A review of MAX series materials: from diversity, synthesis, prediction, properties oriented to functions - Zhang, Jian; Jia, Ru; Tan, Kar Ban; Li, Jiaming; Xu, Shichong; Ying, Guobing; Han, Wenjuan; Lu, Ming (Springer Science and Business Media B.V., 2025)
MAX series materials, as non-van der Waals layered multi-element compounds, contribute remarkable regulated properties and functional dimension, combining the features of metal and ceramic materials due to their inherently laminated crystal structure that Mn+1Xn slabs are intercalated with A element layers. Oriented to the functional requirements of information, intelligence, electrification, and aerospace in the new era, how to accelerate MAX series materials into new quality productive forces? The systematic enhancement of knowledge about MAX series materials is intrinsic to understanding its low-dimensional geometric structure characteristics, and physical and chemical properties, revealing the correlation of composition, structure, and function and further realizing rational design based on simulation and prediction. Diversity also brings complexity to MAX materials research. This review provides substantial tabular information on (I) MAX’s research timeline from 1960 to the present, (II) structure diversity and classification convention, (III) synthesis route exploration, (IV) prediction based on theory and machine learning, (V) properties, and (VI) functional applications. Herein, the researchers can quickly locate research content and recognize connections and differences of MAX series materials. In addition, the research challenges for the future development of MAX series materials are highlighted. (Figure presented.)